MODERN, NEW ASTROPHYSICAL AND COSMOLOGICAL CONCEPTS OF THE ORIGIN OF THE UNIVERSE - O. X. Uzakov (Journal Park Publishing, 2024)
Cosmology is one of the branches of natural science that uses various facts, methods and achievements from astronomy, philosophy, physics and mathematics. The natural scientific basis of this science consists of astronomical observations of the Galaxy, various stellar systems, A. Einstein's theory of relativity, relativistic thermodynamics and various other physical theories. This article outlines astrophysical theories of the structure and dynamics of change in the Metagalaxy, which includes a certain understanding of the properties of the entire Universe. The Universe in the modern picture of the world no longer appears as a being that has become, but as a stream of becoming, generating such fundamental objects of nature as elementary particles, from which the observable hierarchy of levels of organization of the Universe is formed.
Keywords: Hubble's Law, Big Bang theory, quarks, anisotropy, curved space, Universe, cosmology, non-stationary Universe, “red shifts”, galaxy, quantum fluctuations, ultra-high temperatures, matter densities, radiation.